The effect of English Debate on Increasing Communication Skill - Dina Syarifah Nasution (Departement of Mathematics Education, 2023)
The Problem in this research students who have learnt English for six or more years are not as succesfull as the government expects especially in communication. This study intended to understand the impact of Debate in English on improving communication skills, especially oral communication. The type of this research was an experimental study with a pre-experimental design using one-group pre-test-post-test. The population in this research was 60 people divided in to two groups they were experimental and control groups and consisted of 30 people. The data were collected by using observation technique and documentation technique Many studies have reported how practical debate-based English learning activities are in improving overall English. The author found few results of studies that tried to understand the impact of debate-based English training and learning methods on improving and strengthening verbal communication skills. For this reason, we experimented with one of the study groups to prove the extent of the impact of debate-based learning in English and the improvement of communication skills. Our simple step is to experiment by designing the study into two groups; the first is the treatment group, and the other is the control group. We carried out this experiment with two classes of English students at the South Tapanuli educational institute. We have done a series of pretests in both groups.After seven face-to-face meetings for the next treatment class, at the eighth meeting, we gave a final test, also called a posttest, for both groups of students. We have carried out a series of data analyses, and surprisingly the treatment group has a very significant impact compared to the control group. In other words, there has been a change in improving oral communication skills in treating students. The hypothesis testing was done to demonstrate the outcome of the analysis. The null hypothesis was rejected in this example because t0 (3.14) was more significant than the value of the t-table from the table at the significance level of 0.05. (2.000). Consequently, the idea that English discussion significantly influences improving communication skills was developed. This was proven in this study. Hopefully, these findings will contribute new ideas to improving English learning with the discharge activity approach.